Impact of fine arts education on psychological wellbeing of higher education students through moderating role of creativity and self-efficacy - Jin, Xuguang; Ye, Yuan (Frontiers in Psychology, 2022)
The purpose of our research was to explore the impact of fine arts education on psychological wellbeing among undergraduate students through moderating role of creativity and self-efficacy. Art is the most effective medium for expressing human ideals, culture, identity, lifestyles, emotions, and societal experiences. Cross-sectional research was carried out on 376 undergraduates in the 2022–2023 academic year at the public and private Chinese universities, and those students who are currently enrolled in fine arts courses. A link to the Google Doc survey was sent through email and social media channels (i.e., WeChat). The time frame of the data collection was 3 months, from February 2022 to April 2022. While analyzing the obtained data, we used IBM SPSS version 25, which includes both descriptive and inferential statistics. The overall results of the study indicate that the fine arts education positively and significantly influences psychological wellbeing. Moreover, findings also indicate that the creativity and self-efficacy positively and significantly moderate the relationship between fine arts education and psychological wellbeing. The study highlighted the significance of fine arts education in Chinese students. Through this study, students studying in this field should be made more aware of the importance of fine arts education and its link with psychological wellbeing. Further, art courses should be added to the curriculum at different levels of education to boost the creativity and self-efficacy of higher education students in China. Implications for parents, students, and teachers are also discussed.